Spatial Wage Differentials, Human Capital and Labour Precariousness in Ecuador - Moreno, Carlos (2021)
This article aims to assess spatial wage differentials in Ecuador with special attention in education, and two faces of labour precariousness (informality and underemployment). We use Ecuadorian micro-level data from ENEMDU surveys and we decompose the wage gaps between the main metropolitan area and three other regions with lower income. We follow the wage decomposition procedure proposed by Firpo et al. (2009; 2018). For the static analysis (2019), the results show that spatial wage differentials exist almost in all the wage distribution of employees. Some of the explanations of these findings are related with the differences in the skilled workforce and the incidence of informality and/or underemployment.